# 1/6 plus 1 as a fraction 1/6 + 1 as a fraction provides the detailed information about what is 1/6 plus 1 in fraction and decimal form, and the answer with steps to understand how it is being calculated by using different methods.

1/6+1 equals to
1/6 + 1 = (?)
1/6 + 1/1 = [(1 x 1) + (1 x 6)]/(6 x 1)
= (1 + 6)/6
= 7/6
1/6 + 1 = 7/6
1/6 plus 1 is equal to 7/6

where
1/6 is a fraction as an addend,
1 is a fraction as an addend,
7/6 is the sum of 1/6 and 1.

1/6 plus 1 as a decimal
1/6 + 1 = 7/6
7/6 = 1.1667
1/6+1 as a decimal is 1.1667
where
1.1667 is the sum of 1/6 and 1.

For values other than 1/6 plus 1, use this below tool:

## How-to: 1/6 + 1 = ?

The below workout with step by step calculation shows how to find what is 1/6 plus 1 in simplest form by using the following methods:
1. LCM method,
2. Cross multiplication method.

Problem and Workout - LCM Method:
What is 1/6 plus 1 as a fraction?

step 1 Observe the input parameters and what to be found:
Input:
Fraction A: 1/6
Fraction B: 1/1

What to be found?
1/6+1 = ?
Find what's the sum of 1/6 and 1.

step 2 Compare the denominators of fractions 1/6 and 1 to identify whether it is a like or unlike fraction addition. Since the denominators of given fractions 1/6 and 1 are not equal, it is said to be unlike fractions addition.

step 3For unlike fractions addition, find the LCM (least common multiple) of both denominators of fractions 1/6 and 1:
The LCM of 6 and 1 is 6.

step 4 Write the fractions 1/6 and 1 in the addition expression form and multiply LCM with all the numerators and denominators of both fractions.
=1/6+1
=(1 x 6)/(6 x 6)+(1 x 6)/(1 x 6)

step 5 Simplify the expression to have common denominator:
=1/6+6/6

step 6 Take the common values out and rewrite the above expression like the below:
=1/6 x (1/1+6/1)
=1/6 x (1 + 6)

step 7Simplify the above expression further:
=1/6 x 7
=7/6
1/6+1=7/6

Hence,
1/6 plus 1 equals to 7/6 in fraction.

Problem and Workout - Cross Multiplication Method
step 1 Observe the input parameters and what to be found:
Input:
Fraction A: 1/6
Fraction B: 1/1

What to be found?
1/6+1 = ?
Find what's the sum of 1/6 and 1.

step 2 Find the product of numerator of Fraction A and denominator of Fraction B (1 x 1), find the product of numerator of Fraction B and denominator of Fraction A (1 x 6), and find the product of both denominators of Fraction A and Fraction B (6 x 1) and rewrite the equation as like the below:
= (1 x 1) + (1 x 6)/(6 x 1)

step 3 Simplify and rewrite the fraction:
= (1 + 6)/6
1/6+1 = 7/6
Hence,
1/6 plus 1 = 7/6 